Orexinergic pathway as a potential therapeutic candidate for the modulation of glucose homeostasis - Hakizimana, Jean Claude; Izabayo, Pelagie; Izukwizabigenza, Zephyrin; Alagbonsi, Abdullateef Isiaka (Frontiers in Physiology, 2025)
BackgroundGlucose homeostasis is regulated by both central and peripheral systems to maintain metabolic stability during periods of feeding, fasting, and stress. Orexins A and B, hypothalamic neuropeptides traditionally associated with arousal and feeding behavior, are increasingly recognized for their pivotal role in glucose homeostasis via neural and endocrine mechanisms. This review synthesizes the available data orexinergic-glucose pathway.MethodFollowing PRISMA guidelines, a systematic search of PubMed and Wiley Online Library identified original studies (between January 1999 and May 2025) examining orexin’s impact on glucose homeostasis in mammalian models. Molecular mechanisms were analyzed and grouped by tissues: central nervous system (CNS), pancreas, liver, skeletal muscle, adipose or vascular tissue, gut, and whole-body systems.ResultsThirty studies were included. Central orexin neurons integrate glycemic inputs via the autonomic nervous system (ANS). Orexin-A stimulates insulin secretion and β-cell proliferation through OX1R/PI3K/Akt/ERK1/2 signaling. It suppresses hepatic gluconeogenesis via PGC-1α downregulation and enhances insulin sensitivity. In adipose tissue, it promotes GLUT4 translocation and adiponectin via PPARγ/C/EBPα, while protecting endothelium from high-glucose damage via SIRT1/NLRP3 inhibition. In the gut, orexin inhibits SGLT-1-mediated glucose absorption through OX1R/OX2R. Systemic orexin deficiency induces insulin resistance, reversible by treatment.ConclusionThe orexinergic pathway serves as a metabolic integrator, linking central glucose sensing with peripheral utilization. Its context-dependent duality, promoting glucose release in hypoglycemia and insulin sensitivity in hyperglycemia, highlights a unique regulatory role. Orexin receptors are promising therapeutic targets for diabetes and metabolic syndrome. Sex-stratified human studies are needed, as preclinical data reveal marked sexual dimorphism in orexin-mediated glucose regulation, with males exhibiting greater metabolic vulnerability to orexin deficiency.